Implementation of Differentiation Learning Through ClassPoint-Integrated PowerPoint-Based Media at Junior High School 4 Tambang - Permatasari, Silvia; Mustafa, M. Nur; Mustika , Tria Putri; Alfalah , Adib; Rahayu , Anisa Putri; Ramadhan, Ilham (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This study aims to increase teachers' knowledge of differentiated learning, and the use of PowerPoint-based learning media integrated with ClassPoint. Method: Data was collected through initial and final tests to measure teachers' knowledge, feedback questionnaires to evaluate the training experience, and practice observations to assess the application of the material. The collected data were analyzed quantitatively by comparing test results and qualitatively through analysis of feedback and practice observations. Practical Application: Improve teachers' understanding of the concept of differentiated learning and the use of PowerPoint media integrated with ClassPoint, making learning more interactive. Conclusion: The participants were actively involved in the delivery of materials and practices and were satisfied with the training, from the delivery of materials to technical support. The average score of the participants' initial test was 85.00, which increased to 88.00 after the training, indicating an increase in understanding.